Bacterial contamination in a modern operating suite, 2. Effect of a zoning system on contamination of floors and other surfaces. - Hambraeus, A. (Cambridge University Press, 1978)
In this investigation the bacterial contamination of surfaces such as walls and floors in a modern operating suite, together with surfaces of lamps in the operating theatres, and the clogs worn by staff, was studied. Counts of colony-forming units were made on impression plates containing blood-agar with Tween 80 for total bacterial counts, Baird Parker medium with egg yolk and tellurite for Staphylococcus aureus and trypticase peptone agar with neomycin and polymyxin for Clostridium spp. The areas examined were divided into the patients' route to the operating theatre, the staff's route, and the central area containing the operating rooms, anaesthetic rooms, and exit and scrub-up areas. In the patients' route counts of total organisms ranged from about 10000 to 30000/m2; for Staph. aureus the range was from 70 to 540/m2. In the staff's route the highest count was about 70000/m2 in the dressing area, and the numbers of Staph. aureus were about the same as along the patients' route. In the inner zone the counts were somewhat lower for both total organisms and Staph. aureus. Total counts on the floor from all areas of the inner zone were significantly higher just before the second operation than before the first operation on the same day. The total and Staph. aureus counts on walls, floors and lamps were the same after clean operations as after operations classified as "contaminated" or "dirty".